PENGARUH CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN MOBIL TOYOTA YARIS PADA PT. AGUNG TOYOTA JAMBI - Osrita Hapsara; Sakinah AS Sakinah AS (Universitas Batanghari Jambi, 2015)
The purpose of this study is to know how big the influence of Brand Image of car purchase decision on Toyota Yaris PT. Agung Toyota Jambi. The method used in this study is simple regression methods to see the influence of the Brand Image of Toyota Yaris car purchase decision and use the correlation coefficient to see how much influence brand image of Toyota Yaris car purchase decision on PT. Agung Toyota Jambi. Based on the analysis known that the influence of the Brand Image of Toyota Yaris car purchase decision seen from the values of r = 0,166. In addition, based on the calculated correlation coefficient demonstrate the value of r square = 0,155 shows that for 40,8% purchasing decision of Toyota Yaris are influenced by Brand Image while the remaining 59,2% influenced by other factors is not examined. Keyword: influence purchasing decisions, brand image